AN ANALYSIS OF NETWORK EXPANSION TO REPAIR VOLTAGE DROPS ON SULUM FEEDER DISTRIBUTION NETWORK PT PLN (PERSERO) KUALA SIMPANG CUSTOMER SERVICE UNIT - Fadly Rozeta; Hamdani Hamdani; Solly Aryza (Sean Institute, 2022)
In improving the voltage drop, PLN had tried several methods such as adding substations or commonly referred to as insertion substations, but the results are still unsatisfactory, current actions to maintain the quality of electricity distribution are being carried out by PT. PLN Persero Main Unit Aceh Region UP3 Langsa ULP Kuala Simpang is to expand a network by diverting the voltage source from the Pulo Tiga Substation which is 43 km from the Substation to the Terban Substation which is 12 km from the closer Substation so that it can change a voltage, which was initially small because at the end of the network it became much larger because it was at the base of the network which was close to the voltage source itself.Based on the data collected, the Sulum feeder experienced large enough voltage drop, namely 26.74% for the daytime peak load and 19.2% for the night peak load before switching the voltage source. After switching the voltage source, the value of the voltage drop is reduced to 3.6% for peak day loads and 4.1% for peak night loads